Improving the diagnosis of tuberculosis and drug-resistant (including rifampicin heteroresistance) using novel molecular tools in a high-volume programmatic laboratory - Ghebrekristos, Yonas Tesfagabir (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.